2015
DOI: 10.11113/jt.v72.4005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rainfall Effect to Slope Stability in Ulu Klang, Malaysia

Abstract: Malaysia is a country that is located near the equator line with tropical climates which receives high abundant rainfall, averaging 2,400mm annually. This makes Malaysia prone to the landslide events as rainfall is one of the main triggering factors that can cause landslide. Landslides in Malaysia are mainly attributed to frequent and prolonged rainfalls, in many cases associated with monsoon rainfalls. Of these, Ulu Klang area has received the most exposure. The area has constantly hit by fatal landslides sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The series of floods were unusual as the 2006 average rainfall return period was 50 years, while 2007 had more than a 100-year return period. Local weather changes are among the natural causes that triggered the flash flood [35,36].…”
Section: Floodsmentioning
confidence: 99%
“…The series of floods were unusual as the 2006 average rainfall return period was 50 years, while 2007 had more than a 100-year return period. Local weather changes are among the natural causes that triggered the flash flood [35,36].…”
Section: Floodsmentioning
confidence: 99%
“…He also mentions that the ground water level also playing important role in triggering the landslide, which is always overlooks as one of the initial factors of landslide. (Mukhlisin et al 2015) analyzed 15 event of rainfall prompted landslides in Ulu Klang, and found that all of the event were triggered by landslide but some events casual factors were different that was inadequate slope design, improper design, construction method, poor maintenance of the internal drainage system, off slope and retaining structural soil type and slope gradient. In Malaysia most slope failure occurred by manmade slope development in hilly terrain areas, such as highland tower at kualampur in 1993, bukit lanjan rockside in 2003, taman zooview in 2006, and again bukit lanjan at 2014.…”
Section: Class 3 (Landslide Triggering Factors Investigation)mentioning
confidence: 99%
“…Generally, it is expressed by the estimation of factor of safety (FOS), defined as the ratio of the available strength to the strength at failure. There is much research that studied the changes in factor of safety influenced by rainfall, extreme drying, vegetation or earthquake such as Mohd Taib et al [15], Mukhlisin et al [16], Altalhea et al [17], Mukhlisin et al [18], Mukhlisin et al [19], Harianto et al [20], Kristo et al [21] and Fan et al [22] work. In this paper, the stability of slopes is affected by the waste degradation where Babu et al [3] suggested that the value of safe safety factors to guarantee long-term slope stability of the landfill is 1.5-3.0.…”
Section: Factor Of Safetymentioning
confidence: 99%